Knowledge and handling of pesticides by the retailers in the north-eastern part of Bangladesh - Ahmed, Jaher; Mondal, Md. Fuad; Hasan, Md. Mehedi; Ahmod, Md. Moudud (Fundamental and Applied Agriculture, 2024)
The application of pesticides is a common practice against insect pests on different crops in Bangladesh. Usually, pesticide retailers are involved in recommending and selling of pesticides to farmers in Bangladesh. A survey was conducted by interviewing 54 retailers and 150 farmers using semi-structured questionnaire in six upazilas across two districts of the north-eastern part of Bangladesh to know the knowledge and experience of pesticide handling by the retailers and attitudes of farmers towards retailers’ practices. The interviewees were selected randomly. All the retailers were male, and 85.2% of them were involved in personal business. Most of the retailers (94.5%) got their registration from the Upazila Agriculture Officer (UAO). It was observed that 31.5% of retailers have higher secondary education, followed by secondary (25.9%) and primary (18.5%) education. Surprisingly, only a negligible portion of retailers (1.9%) had technical education on pesticides, and the majority of them (68.5%) received only a short training organized by Agriculture Extension Offices and pesticide companies. Moreover, 20.4% of retailers did not participate in any kind of training on insect infestation while 42.6% attended short training. Although almost 60% of farmers reported that retailers are not well trained, 71.4% of farmers replied that retailer’s suggestions about pesticides are effective. A greater percentage of farmers (88.4%) responded that retailers do not visit the farmers field, and 57.8% mentioned that retailers take excess price of pesticide. The standard safety measures (gloves and masks), first-aid kit, and firefighting equipment are not available in most of the retail shops, although 22.2% of shops have poor storage facilities. According to 81.5% retailers, pesticide applications have been increasing over the last 5 years. The overall scenario demonstrates the devastating and inappropriate handling of chemical pesticides without proper knowledge and guidelines. Long-term training of the retailers and strong monitoring of their practices is essential.